2009
DOI: 10.1371/journal.pone.0004188
|View full text |Cite
|
Sign up to set email alerts
|

Host HLA B*Allele-Associated Multi-Clade Gag T-Cell Recognition Correlates with Slow HIV-1 Disease Progression in Antiretroviral Therapy-Naïve Ugandans

Abstract: BackgroundSome HIV infected individuals remain asymptomatic for protracted periods of time in the absence of antiretroviral therapy (ART). Virological control, CD4 T cell loss and HIV-specific responses are some of the key interrelated determinants of HIV-1 disease progression. In this study, possible interactions between viral load, CD4 T cell slopes, host genetics and HIV-specific IFN-γ responses were evaluated in chronically HIV-1-infected adults.Methodolology/Principal FindingsMultilevel regression modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 62 publications
4
25
0
2
Order By: Relevance
“…Specifically, studies have shown that CD8 ϩ T cell responses to HIV-1 Gag are associated with viremia control (25,37,49,54,58,62). Characterization of CD8 ϩ T cell responses correlated with protection from HIV-1 infection needs to be conducted with PBMCs from individuals who are highly exposed but remain uninfected (HESN).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, studies have shown that CD8 ϩ T cell responses to HIV-1 Gag are associated with viremia control (25,37,49,54,58,62). Characterization of CD8 ϩ T cell responses correlated with protection from HIV-1 infection needs to be conducted with PBMCs from individuals who are highly exposed but remain uninfected (HESN).…”
Section: Discussionmentioning
confidence: 99%
“…To deal with the diver- sity of HIV-1 virus, a mosaic vaccine approach has been developed (13,17,20,31,59), and it appears to have enhanced coverage of diverse HIV strains (13,59). In addition to the reports that Gag specific T cell responses are associated with lower viral loads (25,30,37,49,54,58,62,74), studies have suggested that the failure of current vaccine approach may be due to targeting immunodominant variable epitopes and vaccine approaches targeting conserved regions of HIV-1 have been proposed and are under investigation (38,55,73). The narrowly focused antigen presentation of multiple variants by A*01:01 could be advantageous in dealing with viral diversity, in the meantime avoiding the negative effect of immunodominance of mutable epitopes (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atualmente, muitos estudos têm abordado a resposta de células T CD4+ e CD8+ aos peptídeos da Gag do HIV, considerando que a intensa resposta a Gag está associada com proteção (Betts et al, 2005;Price et al, 2009) e com o controle da viremia durante a infecção (Rolland et al, 2008;Huang et al, 2008;Serwanga et al, 2009). Outros fatores corroboram com a seleção da proteína Gag na composição da vacina como por exemplo, a característica de ser um gene relativamente conservado entre as diversas classes e subclasses do HIV-1, além do fato de promover ampla resposta cruzada antiGag entre pacientes infectados por subclasses diferentes de HIV-1 (Bertoletti et al, 1997;Norris et al, 2004).…”
Section: Infectam (Unaids 2008)unclassified
“…Estudos de infecção por HIV têm relatado que a resposta de células T CD4+ e CD8+ aos peptídeos da GAG do HIV está associada com proteção (Betts et al, 2005;Price et al, 2009) e o controle da viremia durante a infecção (Rolland et al, 2008;Huang et al, 2008;Serwanga et al, 2009). Outros fatores que reforçam a escolha da proteína GAG na composição da vacina é por se tratar de um gene relativamente conservado entre as diversas classes e subclasses do HIV-1, permitindo resposta anti-GAG mesmo entre pacientes infectados por diferentes subclasses de HIV-1 (Norris et al, 2004).…”
Section: Vacinas De Dnaunclassified